Fabrication of micro-and nano-particles of drug for pharmaceutical application (I) - Tan, Yong Wah. (2011)
This project aims to improve the solubility of a poorly-water soluble drug, Hesperetin, by fabricating the drug into mico-/nano- particles. Fabrication of the drug particles was done using the two approaches, namely syringe pump precipitation approach and evaporative precipitation of nano-suspension (EPN) respectively; the physiochemical properties of all the samples fabricated has been investigated.